A Study On Customer Buying Behaviour Based On Brand Equity And Satisfaction Towards Organized Retail Stores - Ms. K. Suregka Felix; Dr. M. Hema Nalini (Educational Administration: Theory and Practice, 2024)
The findings elucidate that brand equity is significantly differing amidst profile of customers in organized retail outlets. Brand awareness, brand association, perceived quality and brand loyalty have significant and positive influence on buying behaviour of customers in organized retail stores. Brand equity, buying behaviour and satisfaction of customers in organized retail stores are positively and significantly inter related with each other. Thus, all the hypotheses are supported by the outcomes of this study. Organized retail stores should adopt efficient advertisement and sales promotional strategies for improving awareness and association of brands among customers. In addition, organized retail stores should take necessary efforts to improve perceived quality and brand loyalty of customers and they must create better image about brands among customers that makes them to distinguish brands along with superiority of a brand over other competitive brands of organized retail stores and make them loyal towards them and these improve further buying behaviour and satisfaction of customers in organized retail stores.